Economic Aspects of Mangrol Groundnut Producer Company Ltd.: Deployment of Groundnut Growers Towards the Formation of FPO in Mangrol Taluka of Junagadh District - Panchani, Pooja; Birari, Uday (Journal of Agricultural Extension Management, 2022)
The Farmer Producer Organization is hybridizing of cooperative society and private limited company. Most of the initiatives on producer companies were started and promoted by NGOs/ development agencies/ sponsoring organizations. The core aim of FPO is to improve member farmers’ income and standard of living by purchasing farm produce from them and selling the products after value addition in the market. This study was conducted to identify the economic benefits of FPOs for farmers, based on the actual trial of 100 Kgs groundnut processing. The tabular method was used to measure the economic aspects of Mangrol Groundnut Producer Company. From the study of cost and returns of groundnut processing, it was observed that the business of value addition was profitable for the Company by the traditional method done through process outsourcing. However, it would be more profitable by establishing its processing plant by the traditional method.